Implementation of the Pepeling Program Policy (Mobile Tax Payment Service) in Increasing Regional Original Revenue in Serang City - Pramesti, Nadifi Silviana; Stiawati, Titi; Rulinawaty (Universitas Medan Area, 2025)
Serang City, as the capital of Banten Province, recorded the lowest regional revenue (PAD) among other cities/regencies in the province from 2018 to 2020. The low understanding of taxpayers regarding tax obligations and limited investment in Serang City have contributed to its low PAD. This condition urged the Serang City Government to innovate and implement the Pipeline Program (Mobile Tax Payment Services) initiated by the Regional Revenue Agency to enhance regional revenue. However, challenges persist in its implementation, including limited infrastructure and human resource capacity. This study aims to analyze the implementation of the Pipeline Program policy in increasing regional revenue in Serang City. Using a qualitative research design with a descriptive and inductive approach, data collection methods included interviews, observations, and documentation. The study applies Van Metter and Van Horn's theory, focusing on six indicators: policy standards and objectives, resources, inter-organizational communication and implementing activities, characteristics of implementing agencies, socio-economic and political conditions, and implementers' dispositions. The Pipeline Program is a payment channel designed to optimize public service delivery and provide tax education, especially for taxpayers in remote areas. The program contributed to PAD growth by 0.3% in 2021, 0.5% in 2022, and 2.4% in 2023. Enhancing operational vehicles, human resource quality and quantity, and continuous optimism are necessary to ensure Serang City's PAD steadily increases, removing its status as one of the lowest PAD contributors in Banten Province.